Psychosexual and depression disorders in infertile female referring to Mashhad Infertility Treatment Center - MR Sargolzaee; F Moharreri; HR Arshadi; K Javadi; S Karimi; MR Fayyazi-bordbar (JRI, 2001)
Infertility is a common problem which about 15-20% of couples in their fertility life suffer form it. Though the role of psychological problems as etiologic factors for infertility is in doubt but psychogenic variables and life-style absolutely play important role in infertility, on the other hand infertility itself can cause different psychological reactions like depression in individual. Therefore researchers decided to evaluate the prevalence of psychosexual disorders and the rate of depression in fertile couples and determine its correlation with infertility. Research was across sectional study and was done during one month. 30 infertile women were selected randomized among infertile couples who were admitted in Mashhad Infertility Treatment Center (Montaserieh Hospital). These persons filled Global Sexual Functioning scale (GSF) and Hamiltion’s rating scale for depression and answered a questionnaire which included information such as: age, education, job, duration of marriage and infertility treatment. According to Hamilton scale, 7 persons (%23/3) had mild depression, 16 persons (%53/3) had moderate depression, 6 persons (%20) were deeply depressed and only one person had normal mood. On the other hand sexual dysfunction were more common in couples with higher age difference. There was no correlation between age mean difference of the couples and sever and moderat depression (t=1.7, r=-0.306), but it was correlated with duration of infertility treatment (t=-2.59, r=-0.44, P<0.05), this shows the importance of more psychological attention at early stages of infertility diagnosis. There is no correlation between depression and sexual dysfunction (r=0.028) which shows sexual dysfunction in infertile couples are independent from depression.
Keywords: Infertility, Infertile women, Depression, Sexual disorders